REFORMASI SYARI’AH DAN WACANA HAK ASASI MANUSIA (Studi Pemikiran Hukum Abdullah An-Na’m) - Jamhari Jamhari (Nurani, 2015)
Abstract: Abdullah An-Na'im is the figure of the modern thinker; his work is a good starting point of radical Islam modernist and fundamentalist position that both of them dominate contemporary thinking in the Islamic world. According to Shari'ah are no longer relevant and no longer adequate for the needs of modern society, it has led to serious problems when dealing with human rights standards. An-Na'im transformed basic understandings of traditional Islamic law. In terms of Shari'ah, An-Na'im advocated a new system of Islamic law which is believed to provide a thorough foundation more in line with Islamic life in the contemporary world. This article will explore formulation in the face of political structures, social order, criminal law, international law and human rights. ملخص: عبد لله النعیم ھو الرقم المفكر المعاصر؛ عملھ ھو نقطة انطلاق جیدة ل الحداثیة الإسلام المتطرفة و الموقف الأصولي أن كلا منھم تھیمن على التفكیر المعاصر في العالم الإسلامي . وفقا ل أحكام الشریعة الإسلامیة لم تعد مناسبة والتي لم تعد كافیة لتلبیة احتیاجات المجتمع الحدیث، وقد أدى ذلك إلى مشاكل خطیرة عند التعامل مع معاییر حقوق الإنسان. النعیم تتحول التفاھمات الأساسیة للقانون الإسلامي التقلیدي. من ناحیة الشریعة الإسلامیة، دعا النعیم نظام جدید للشریعة الإسلامیة التي یعتقد أنھا توفر أساسا شاملا أكثر انسجاما مع الحیاة الإسلامیة في العالم المعاصر. ھذه المادة سوف تستكشف صیاغة في مواجھة البنى السیاسیة والنظام الاجتماعي، والقانون الجنائي والقانون الدولي و حقوق الإنسان. Kata Kunci : Reformasi Syariah, Abdullah An-Na’im